The Effect of Competency and Ethics Independence on The Performance of inspectorates (Study of the Tana Toraja District Inspectorate) - Trifani Diviyana Putri; David Adechandra Ashedica Pesudo (Budapest International Research and Critics University, 2022)
The purpose of this study is to find out how the influence of Indepedence, Competence and Ethics on the Performance of the Tana Toraja District Inspectorate. The population of this study was all auditors at the Tana Toraja District Inspectorate Office which amounted to 33 people. Sample selection is used by the saturation sampling method, where sampling is carried out to all members of the population. The data obtained will then be tested using the help of SPSS software. The independent variables used are Independence, Competence, Ethics and the dependent variable is the Performance of the Inspectorate. The results of the research conducted showed that Competencies with a sig value (0.006 < 0.5) and Ethics with a sig value (0.004 < 0.05) had a positive and significant effect on the performance of the inspectorate. Independence has no significant effect on the performance of the inspectorate with a sig. (0.095 > 0.05).